2018
DOI: 10.1177/2036361318782626
|View full text |Cite
|
Sign up to set email alerts
|

Acral myxoinflammatory fibroblastic sarcoma with hybrid features of hemosiderotic fibrolipomatous tumor occurring 10 years after renal transplantation

Abstract: Myxoinflammatory fibroblastic sarcoma is a rare malignant soft tissue neoplasm that typically arises on the distal extremities of adults. It usually behaves in a low-grade manner and its characteristic histology is of a lobulated proliferation of moderately atypical spindled to epithelioid cells, vacuolated cells, and enlarged or bizarre cells with prominent nucleoli, dispersed within myxoid stroma containing a mixed inflammatory cell infiltrate. The etiology of myxoinflammatory fibroblastic sarcoma remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Only one study has reported a history of renal transplantation in one case. 8 In the macroscopic examination, consistency is myxoid to hard in subcutaneous tissue with well‐defined or infiltrative borders. 1 , 3 , 7 MIFS has variegated and heterogeneous microscopic findings and consists of a multinodular appearance with three components: inflammatory cells, areas of fibrosis or hyalinized stroma, and areas of the extracellular myxoid matrix with tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study has reported a history of renal transplantation in one case. 8 In the macroscopic examination, consistency is myxoid to hard in subcutaneous tissue with well‐defined or infiltrative borders. 1 , 3 , 7 MIFS has variegated and heterogeneous microscopic findings and consists of a multinodular appearance with three components: inflammatory cells, areas of fibrosis or hyalinized stroma, and areas of the extracellular myxoid matrix with tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 3 , 7 MIFS has variegated and heterogeneous microscopic findings and consists of a multinodular appearance with three components: inflammatory cells, areas of fibrosis or hyalinized stroma, and areas of the extracellular myxoid matrix with tumor cells. 2 , 8 Tumor cells are atypical epithelioid and spindle cells resembling Reed‐Sternberg cells, multivacuolated cells resembling lipoblast cells, and ganglion cells without mitosis. 2 , 3 , 8 Heterogeneous components of MIFS in small biopsy specimens may be the cause of misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prominent inflammatory component seen in MIFS has led to the suggestion that mediators of chronic inflammation, including various cytokines, may be implicated in its development. 7,8 Histologically, MIFS is characteristically a multinodular lesion composed of hypocellular and hypercellular areas comprising of atypical spindle to epithelioid cells, vacuolated fibroblasts mimicking lipoblasts (pseudolipoblasts), and large pleomorphic virocyte-like or Reed-Sternberglike cells within prominent myxoid stroma containing a mixed inflammatory cell population, variable hemosiderin deposition, and fibrosis. [7][8][9] The mitotic activity is usually low.…”
Section: Discussionmentioning
confidence: 99%
“…5 Genetically, MIFS has been associated with a marker/ ring chromosome 3 with 3p amplicons 10 as well as with a characteristic translocation, t(1;10)(p22;q24) with rearrangements of TGFBR3 and MGEA5 on chromosomes 1p22 and 10q24. 8 Differential diagnosis includes a wide range of conditions including both benign and malignant such as tenosynovitis, giant cell tumor of the tendon sheath, inflammatory myofibroblastic tumor, liposarcoma, epithelioid sarcoma, and myxoid malignant fibrous histiocytoma. MIFS is rather difficult to diagnose due to its heterogeneous histology and therefore all the above-mentioned conditions need to be excluded before conclusion of this diagnosis.…”
Section: Discussionmentioning
confidence: 99%